A Comparative Study of Students' Learning Interests Using Scrapbook Media and Lapbook Media In Elementary School - Lidia Nur Tanti, Lidia Nur Tanti; Nafiah; Afib Rulyansah; Muslimin Ibrahim (Universitas Nahdatul Ulama Surabaya, 2025)
This study aims to compare students’ learning interest in Pancasila Education using two types of instructional media scrapbook and lapbook based on the ARCS model (Attention, Relevance, Confidence, Satisfaction). This research employed a quantitative approach with a comparative design. The subjects consisted of 52 fourth-grade students at SDN 1 Semampirejo, with Class IVA using scrapbook media and Class IVB using lapbook media. The primary instrument was a learning interest questionnaire constructed based on the ARCS indicators and measured using the Guttman scale. The normality test showed that the data were normally distributed, while the homogeneity test indicated that both groups had equal variances (p > 0.05). The findings revealed that both media were effective in increasing students’ learning interest, with both groups reaching a very high category. The lapbook group scored higher in relevance (92%), confidence (97%), and satisfaction (95%). However, the independent sample t-test indicated no statistically significant difference between the two groups (p = 0.574). These results suggest that while both media are effective, lapbooks provide a more interactive and enjoyable learning experience. This study acknowledges several limitations, including a small sample size and the absence of a pre-test.